STUDI KOMPARATIF TENTANG KARAKTER TOLERANSI ANTARA SISWA LAKI-LAKI DENGAN SISWA PEREMPUAN KELAS X DI SMA NEGERI 1 TUALANG - Raie Restu Mentari; Ahmad Eddison; Haryono Haryono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research is motivated by the fading of students' tolerant attitudes male students and female students. From the symptoms at school, it can be seen that the tolerance of students is quite low in several aspects. Which psychologically men and women differ both physically and psychologically. The formulation of the problem in this study is "Are there differences in the character of tolerance between male students and female students of class X in SMA Negeri 1 Tualang?". This study aims to determine differences in the character of tolerance between male students and female students of class X at SMA Negeri 1 Tualang. The benefits of research as a reference in knowing the differences in tolerance between male and female students. This research was conducted at SMA Negeri 1 Tualang from May to August 2020. This research is a quantitative research with a comparative descriptive approach which is the population in this study as many as 376 students. The sample technique is proportional random sample using the Yamane formula so that the number of samples is 78 respondents, 39 male students and 39 female students. Data collection techniques are questionnaires or tolerance questionnaires through Google Forms and interviews. Based on the results of the study, it was found that the tolerance character of male students in class X SMA Negeri 1 Tualang was "very high". This is evidenced by the results of the calculation of respondents' answers in the range> 75.01-100% with a percentage of 80.64%. Based on the criteria in the high or low percentage category according to Arikunto (2009), the percentage of the total score is included in the "Very High" category. Meanwhile, the character of tolerance for female students of class X SMA Negeri 1 Tualang is also in the "Very High" category. This is evidenced by the results of the calculation of respondents' answers in the range> 75.01-100% with a percentage of 83.58%. Based on the difference test table supported by SPSS 26 Comparative Study of Character Tolerance between Male Students and Female Students in class X SMA Negeri 1 Tualang in the equal variances assumed the Sig. (2-tailed) 0.044 <0.05, so as the basis for decision making in the independent sample t test, it can be concluded that Ho is rejected and Ha is accepted. Thus it can be concluded that there is a significant difference between the tolerance of male students and female students of class X SMA Negeri 1 Tualang.Key Words: Character Tolerance, Male Students, Female Students